Tenth Five Year Plan (2002-07) Draft Annual Plan 2005-06 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 2005)
Draft Annual Plan 2005-06 Union Territory of Pondicherry Major Head and Minor Head Development, Agriculture and Allied Activities, Soil Water Conversation, Rural Development, Food Storage Warehouse, Crop Husbandry Horticulture, Agricultural Research Education, Women & Child Development.
Government of Pondicherry Planning and Research Department
Keywords: Proposed Outlays; Physical Targets and Achievements; A Proposal for Spillover and Ongoing Progrramme; Proposals for Maximizing Benefits Of Completed Progrramme; Proposal For New Schemes Progrramme; Regarding Externally Aided Projects; Outlays By Heads of Development for District Plans; Special Component Plan Physical Targets; Women Sub-Plan - Financial Outlays; Tribal Sub-Plan - Physical Targets